Social Support Theory for Predicting Stress, Anxiety, and Job Burnout of Healthcare Workers in the Post-pandemic COVID-19 - Masoumeh Mohammadi Khanqah; Fataneh Bakhshi; Asieh Ashouri; Abolhasan Afkar (Caspian Journal of Health Research)
Background: The COVID-19 pandemic created substantial mental health challenges for healthcare workers, leading to elevated levels of stress, anxiety, and burnout. Social support is a critical factor in alleviating these psychological impacts, helping individuals to manage stress effectively. Objectives: This study aimed to explore the relationship between perceived social support and levels of stress, anxiety, and burnout among healthcare workers in Ardabil, Iran, in the post-COVID-19 period of 2023. Materials & Methods: A cross-sectional study was conducted among 216 healthcare workers, selected via stratified random sampling based on job roles. Participants completed demographic questionnaires, the depression anxiety sress scale, the Maslach burnout inventory, and the multidimensional scale of perceived social support. data analysis included descriptive statistics and multiple linear regression models using SPSS software, version 22. Results: The Mean±SD scores for stress and anxiety were 9.11±5.64 and 6.44±5.23, respectively, with a median burnout score of 38 (IQR: 26-50). The mean perceived social support score was 45.87±8.75. Multiple regression model including significant demographic and confounding variables along with perceived social support explained 25% of the variance in stress, 16% in anxiety, and 23% in burnout. The workplace environment was significantly associated with both perceived social support and mental health outcomes. Conclusion: Perceived social support is inversely associated with stress, anxiety, and burnout among healthcare workers. Workers in metropolitan areas reported lower social support and higher psychological distress. Interventions to strengthen social support may benefit mental health and help reduce burnout among healthcare professionals.